Kedudukan Penegak Hukum Penyidik Terhadap Tindak Pidana Pencucian Uang Dalam Militer di Indonesia - Fitrianingrum, Avisa; Badriyah, Siti Malikhatun (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Crimes that are classified as extraordinary crimes are money laundering which can disrupt the economic and structural stability of the country. This offense can be committed by active members of the TNI. The investigation into him is an integral part of the criminal justice system. The aim of this research is regarding the role and position of legal investigators in dealing with TPPU involving the military in Indonesia. The method used in this research is normative by reviewing literature and legal sources, including legal principles, positive law, legal regulations, and legal principles. Research findings show that if there are members of the TNI who commit general offenses (including TPPU), then the investigative authority in money laundering cases involving the Indonesian military can come from the POLRI, TNI, Attorney General's Office, or other agencies that have investigative and prosecutorial authority. All parties must coordinate to ensure that this case is handled carefully and transparently in accordance with applicable law.